Automorphisms and isomorphisms of Jha-Johnson semifields obtained from skew polynomial rings. Issue 10 (3rd October 2018) - Brown, Christian; Pumplün, Susanne; Steele, Andrew
ABSTRACT: We study the automorphisms of Jha-Johnson semifields obtained from a right invariant irreducible twisted polynomial f ∈ K [ t ; σ ], whereK = 𝔽 q n is a finite field and σ an automorphism of K of order n, with a particular emphasis on inner automorphisms and the automorphisms of Sandler and Hughes-Kleinfeld semifields. We include the automorphisms of some Knuth semifields (which do not arise from skew polynomial rings). Isomorphism between Jha-Johnson semifields are considered as well.